Horta em tempo de pandemia - Almeida , Gisele Rodrigues de; Araujo, Jucelio Alexandre; Freitas, Marcos Rodrigues de; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf